Joint attention is intact even when visuospatial working memory is occupied. (January 2019) - Yokoyama, Takemasa; Kato, Ryosuke; Inoue, Kazuya; Takeda, Yuji
Abstract: The gaze of another modulates and shifts an observer's spatial attention toward this gaze direction. This phenomenon is termed joint attention. Although previous studies found joint attention was induced during a spatial working memory task, it remains an open question whether spatial working memory interferes with joint attention. To address this question, we conducted a dual task paradigm consisting of gaze cuing and spatial working memory tasks. The gaze cuing task requires that participants respond to the location of an abrupt onset of a target while ignoring the gaze of a facial image located at the center of the display. In the spatial working memory task, participants memorized two or three locations of small dots and judged whether these locations changed in the probe screen. In the dual task condition, while participants were maintaining spatial information of the spatial working memory task, they performed the gaze cuing task. In Experiment 1, maintaining spatial information did not impair the magnitude of joint attention. In Experiment 2, we increased load of spatial working memory task, and still observed results similar to Experiment 1. In Experiment 3, we replicated the findings in Experiment 1 when an identification task was conducted. In addition, we measured electrooculographic signals to investigate eye movements of participants during the task. The study provides that joint attention is intact even if spatial working memory is occupied.